2003
DOI: 10.1038/nm896
|View full text |Cite
|
Sign up to set email alerts
|

SOCS-3 regulates onset and maintenance of TH2-mediated allergic responses

Abstract: Members of the suppressor of cytokine signaling (SOCS) family are involved in the pathogenesis of many inflammatory diseases. SOCS-3 is predominantly expressed in T-helper type 2 (T(H)2) cells, but its role in T(H)2-related allergic diseases remains to be investigated. In this study we provide a strong correlation between SOCS-3 expression and the pathology of asthma and atopic dermatitis, as well as serum IgE levels in allergic human patients. SOCS-3 transgenic mice showed increased T(H)2 responses and multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
345
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(370 citation statements)
references
References 36 publications
23
345
2
Order By: Relevance
“…After 48 h, the effects of IL-12 were clear and altogether 41 genes became regulated by IL-12 (Table II). Among these were only a few genes, such as SOCS3, CEBPB, and IL-7R that have a previously described role in Th1 and Th2 cell responses (13,19,20). Most of the genes regulated by IL-12 were also regulated by IL-4 and/or activation alone (Fig.…”
Section: The Slow Response To Il-12mentioning
confidence: 85%
“…After 48 h, the effects of IL-12 were clear and altogether 41 genes became regulated by IL-12 (Table II). Among these were only a few genes, such as SOCS3, CEBPB, and IL-7R that have a previously described role in Th1 and Th2 cell responses (13,19,20). Most of the genes regulated by IL-12 were also regulated by IL-4 and/or activation alone (Fig.…”
Section: The Slow Response To Il-12mentioning
confidence: 85%
“…These proteins were recently demonstrated to be able to inhibit IL-4-induced expression of Eotaxin-3/CCL26 [48], another chemokine. Further, SOCS-1 and SOCS-3 were shown to be inducible by IL-4 [29,38,49], and SOCS-3 appears to be involved in the regulation of allergic responses [50]. The prominent role TARC/CCL17 plays in allergic diseases calls for additional studies to elucidate the negative regulatory mechanisms of its expression.…”
Section: Ccl17 In T Cells and To Characterize The Regulatory Promotermentioning
confidence: 99%
“…Since 1997 [5], numerous studies have identified that SOCS-3 acts as a negative-feedback inhibitor to suppress the cytokine receptor signalling, for example, in myeloid cells, SOCS-3 is a key negative regulator of G-CSF signalling [6]. It negatively regulates IL-2 signalling [7] and IL-2 production via CD28 signalling [8], inhibits IL-6 signalling in macrophages [9e11], and promotes Th2 development by inhibiting IL-12 mediated STAT4 activation in T cells [12]. The knocking down SOCS-3 gene in T helper cells reduced the immune responses, and resulted in the overexpression of IL-10 and transforming growth factor [13].…”
Section: Introductionmentioning
confidence: 99%